(untitled) (Research, Society and Development, 2020)
The present study aims to determine the geographical distribution of HbS, HbC, HbD variant hemoglobins, as well as patients diagnosed with sickle cell disease in a public health laboratory in the municipality of Teresina - Piauí, based on the neonatal screening program. A descriptive, cross-sectional, observational and retrospective study with a quantitative approach was conducted, based on secondary data provided by the Central Public Health Laboratory of the State of Piauí (LACEN-PI). The neonatal screening databases were analyzed, and all newborns who underwent the neonatal screening test in the agreed collection network from January 2018 to August 2019 were sampled. About 17,236 samples were analyzed from the municipality of Teresina (25,3% total analyzed) and organized according to the municipal administrative zones. This study allowed us to draw a map in the municipality of teresinense showing the areas with the highest incidence of hemoglobinopathies.